Efektivitas Implementasi SOTK Pusinafis Bareskrim Polri Di Kewilayahan - Aziz, M Asrul; Suprapto, Heri (Jurnal Litbang Polri, 2022)
This research was conducted with a mix method research approach with data collection techniques for distributing questionnaires, interviews, Focus Group Discussions (FGD) and document studies. The research instrument was a questionnaire and an interview guide. Quantitative research respondents are officials and personnel assigned to the Identification Section (Siident) at the Polda level and Identification Affairs (Urident) at the Polres level. Qualitative research informants were officials of HR, Rorena, Rolog, Ditreskrimum, Ditreskrimsus, Ditnarkoba, Ditintelkam, Ditlantas, Biddokkes, Bidlabfor for the Polda level as well as officials for the HR Department, Baglog, Bagren, Satreskrim, Satnarkoba, Satlantas, Satintelkam for the Polres level.